Sistem Pendukung Keputusan Menentukan Prioritas Tujuan Wisata Daerah pada Kabupaten Karo Menggunakan TOPSIS - Jimmi Herdianda Gurusinga; Bosker Sinaga (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
There are approximately 20 tourist objects in the Karo Regency area that are close to each other, such as Gundaling Hill, Lumbini Nature Park, Fun Land Mickey Holiday and other places. Priority for visiting tourist areas really needs to be determined for time and cost efficiency and so that visitors can reach other tourist attractions around Tanah Karo. The problem in this research is designing a Decision Support System to determine the priority of regional tourist destinations in Karo Regency using the TOPSIS method. Determination of the weight of each criterion obtained from processing the interview data. The weight of the criteria to determine the preferred criteria. The greater the weight, the more priority. Weights for each criteria for determining priority destination of tourist attractions, Distance from Berastagi (weight 30%), Facilities and Facilities (weight 15%), Access (15%), Type of Tourism (weight 20%), Entrance Fee (Weight 15%), Culinary (weight 5%), and internet network (5%).